INHIBITORY EFFECTS OF DANGKE, A FERMENTED DAIRY PRODUCT FROM ENREKANG, ON STREPTOCOCCUS GROWTH IN DENTAL PLAQUE - Hatta, Ridhayani; Samad, Rasmidar; Mappangara, Surijana; Pratama, Mohamad Arif Budiman Putra; Nurfianti, Nurfianti; Setianingtyas, Prastiwi; Zakki, M (LPPM Universitas Jambi, 2026)
Dairy products are known for their non-cariogenic properties and have even been reported to inhibit the attachment of cariogenic bacteria such as Streptococcus spp. on dental plaque. Dangke, a traditional dairy product from Enrekang, South Sulawesi, with a high protein content of up to 17.20%, dangke is considered a non-cariogenic food. This study aimed to evaluate the in vitro efficacy of Dangke in reducing Streptococcus levels in dental plaque. The evaluation of Dangke implicates the use of traditional dairy products in oral health. This quasi-experimental study used a post-test-only control-group design with 15 subjects selected via simple random sampling. Subjects were divided into two groups: a treatment group that consumed Dangke and a control group that consumed cheddar cheese. Plaque samples were collected twice from each subject—immediately after consumption (T1) and two hours later (T2)—resulting in 30 samples per group. The Streptococcus colony counts were analyzed at the Microbiology Laboratory, Faculty of Medicine, Hasanuddin University. At T1, the mean colony counts were 19.44 CFU/mL for the Dangke group and 31.56 CFU/mL for the Cheddar group. At T2, the counts were 2.44 and 27.56 CFU/mL, respectively. A statistically significant reduction was observed in the Dangke group (p = 0.028), while no significant change was seen in the Cheddar group (p = 0.746). Dangke demonstrated a significant antimicrobial effect against Streptococcus in dental plaque and may serve as a natural cariostatic agent, providing new insights into the potential of local food products for caries prevention.